Peran HPMM Cabang Alla Dalam Mengawal Kinerja Pemerintah Di Kabupaten Enrekang - Muhammad Nawir; Suardi Suardi (Universitas of Muhammadiyah Makassar, 2017)
This study aims to identify the role of HPMM Branch Alla on the performance of government in Enrekang Regency and to know the impacts of the community on the role of HPMM Branch Alla. The type of this research is descriptive qualitative method, data collection is used by observation, interview, documentation technique from photograph result, sound recording and archive owned by local government. The results of this study indicate that HPMM's role in community empowerment is to facilitate community preparation, bridging the interests of the community and the government, thus conflicts can be detected early. Another role is advocacy that is directed to the correlation of deviations, while the main mission is how to make the community self-governing and not to leave everything to be administered by the government. This means that HPMM Branch Alla became a government colleague in Enrekang Regency. For the social impact is divided into two, namely positive impact is communication, delivery of issues and policy making that is not in accordance with the government is easy with the help of HPMM Branch Alla as a facilitator (facilitator and motivator) and memperhatiakn elements of community participation. While the negative impact is with the presence of several parties / people who take personal advantage on behalf of the interests of the organization and the aspirations of the community. And some people who also have college kids assume that the organization will disturb or slow the period of college for their children.Keywords: Role, HPMM Alla Branch, Performance